Differences in the Associations Between Memory Complaints and Depressive Symptoms Among Black and White Older Adults. (9th August 2018) - Hill, Nikki L; Mogle, Jacqueline; Bhargava, Sakshi; Whitaker, Emily; Bhang, Iris; Capuano, Ana W; Arvanitakis, Zoe; Bennett, David A; Barnes, Lisa L
Abstract: Objective: To test whether race (specifically Black or White) moderates the relationship between memory complaints and depressive symptoms in cognitively normal older adults, and if these relationships vary by memory complaint characteristics. Methods: Data from Black ( n = 551) and White ( n = 1, 158) cognitively intact participants ( M age = 77.1, SD = 7.5; 76.6% female) in the Minority Aging Research Study and the Rush Memory and Aging Project were used. Participants completed annual clinical evaluations, including the Center for Epidemiologic Studies Depression scale and two memory complaint questions, over periods of up to 18 years. Ordinal mixed effects models were used to examine within-person relationships between memory complaints and depressive symptoms over time, as well as whether race moderated these associations. Results: Reports of greater memory change over time were associated with more depressive symptoms for both Black and White older adults. However, reports of greater frequency of memory problems were related to depressive symptoms for Black older adults only. Conclusion: Findings suggest differential associations between memory complaints and depressive symptoms in cognitively normal Black and White older adults and call for future research to examine the influence of race and related factors on memory complaints and depressive symptoms.